2012
DOI: 10.1016/j.bpj.2012.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Self-Complementarity within Proteins: Bridging the Gap between Binding and Folding

Abstract: Complementarity, in terms of both shape and electrostatic potential, has been quantitatively estimated at proteinprotein interfaces and used extensively to predict the specific geometry of association between interacting proteins. In this work, we attempted to place both binding and folding on a common conceptual platform based on complementarity. To that end, we estimated (for the first time to our knowledge) electrostatic complementarity (E m) for residues buried within proteins. E m measures the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 36 publications
(100 citation statements)
references
References 55 publications
4
96
0
Order By: Relevance
“…The basic methodology has already been reported. 1 Briefly, the Complementarity Plot (CP) estimates the shape and electrostatic complementarity of interior residues of a globular protein and is a sensitive indicator of their harmony or disharmony with regard to the short and long range forces sustaining the native fold. A correctly determined natively folded protein structure should have optimal packing between its buried side-chains and absence of destabilizing unbalanced electric fields within the interior of the molecule.…”
Section: Abstract: Complementarity Packing and Electrostatics Strucmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic methodology has already been reported. 1 Briefly, the Complementarity Plot (CP) estimates the shape and electrostatic complementarity of interior residues of a globular protein and is a sensitive indicator of their harmony or disharmony with regard to the short and long range forces sustaining the native fold. A correctly determined natively folded protein structure should have optimal packing between its buried side-chains and absence of destabilizing unbalanced electric fields within the interior of the molecule.…”
Section: Abstract: Complementarity Packing and Electrostatics Strucmentioning
confidence: 99%
“…For electrostatic complementarity (E sc m ), the electrostatic potential of the molecular surface was estimated using the finite difference Poisson-Boltzmann method as implemented in DelPhi. 5 The potential on the side-chain surface points of a buried residue was then computed twice, 1 first, due to all atoms of the target residue and second as a function of all atoms from the rest of the polypeptide chain (excluding the target). Thus, each surface point was tagged with two values of electrostatic potential.…”
Section: Abstract: Complementarity Packing and Electrostatics Strucmentioning
confidence: 99%
See 1 more Smart Citation
“…The Complementarity plot (CP) is an established graphical structure validation tool in the field of protein science originally proposed for globular proteins [1][2][3] and later extended for experimentally solved protein co-complexes [4]. So far, this has been constructed and applied to analyze complementarity in a residue-wise manner in proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The subject has been further complicated by paradoxical observations like the presence of ionic groups in the hydrophobic protein interior without having to adapt to any specialized structures to get stabilized, demanding a considerably higher effect experienced locally at these sites than can be accounted for by the low dielectric constant traditionally assigned to represent the hydrophobic protein interior in continuum models [10]. Primarily contributed by this 'dielectric problem', electrostatic complementarity of individual amino acid residues (Em) within a folded protein chain remained undetermined, until the problem was finally adequately addressed by the same study [1] that put forward the Complementarity Plot (CP). Briefly, the study had shown that electrostatic complementarity (being a correlation function between two troughs of potential values) is independent of any single dielectric constant assigned to the protein interior, treated as the internal dielectric of the continuum [1].…”
Section: Introductionmentioning
confidence: 99%